Infectivity and pathogenicity of Cryptosporidium andersoni to a novel host, southern multimammate mouse (Mastomys coucha) - Kvác, Martin; Ondrácková, Zuzana; Kvetonová, Dana; Sak, Bohumil; Vítovec, Jirí (Veterinary parasitology, 2007)
The infectivity and pathogenicity of Cryptosporidium andersoni (bovine isolate) for neonatal and adult southern multimammate mice (Mastomys coucha) was studied using transmission experiments. C. andersoni isolate used in this study was not infective for BALB/c mice, but experimental infection proved susceptibility of neonatal and adult M. coucha to the infection. The prepatent period was 20-24 days, the patent period varied between 46 and 59 days. No signs of clinical illness or macroscopic findings were detected in infected animals. Cryptosporidium developmental stages were detected only in the glandular part of the stomach of M. coucha in histological sections stained with Wolbach's modification of Giemsa and using immunofluorecence. Histopathological changes were characterized by dilatation and epithelial metaplasia of infected gastric glands without inflammatory response in the lamina propria. Neonatal M. coucha were more susceptible to C. andersoni infection than adults. M. coucha seems to be a useful laboratory model for study of C. andersoni infection.
Keywords: Feces; Random Allocation; Mice, Inbred BALB C; Animals, Newborn; Cryptosporidium; Cryptosporidiosis; Time Factors; Gastric Mucosa; náchylnost k nemoci; Rodent Diseases; Mice; novorozená zvířata; Murinae; Parasite Egg Count; věkové faktory; RNA ribozomální 18S; nemoci hlodavců; zvířata; feces; RNA, Ribosomal, 18S; počet parazitárních vajíček; náhodné rozdělení; myši inbrední BALB C; časové faktory; Disease Susceptibility; Species Specificity; myši; RNA protozoální; Age Factors; žaludeční sliznice; druhová specificita; kryptosporidióza; RNA, Protozoan; Animals